Penguatan kapasitas kelembagaan gapoktan melalui pembentukan koperasi pertanian - Fitriani Fitriani (Faculty of Social and Political Science, Universitas Airlangga, 2015)
Gapoktan or Farmers Group constructed with a focus on improving agricultural production. Gapoktan generally face problems such as limited access to capital, technology and markets. A lack of communication and coordination between the farmer and board member Gapoktan also cause ineffectiveness in Gapoktan performance. This study aims to identify the fusion process and consolidation of institutions Gapoktan become new economic institutions as agricultural cooperatives, also to discover the prerequisite conditions and the necessary support in the new cooperative institutions manifest in District Adiluwih. Methods RRA (rapid rural appraisal) and FGDs conducted to produce concrete solutions for Gapoktan institutional problem resolution. Literacy exploration is an important part in analyzing the problems solving. The finding concluded that the fusion of Gapoktan to cooperative institution took place gradually. The new cooperative called LKMA Sharia Adi Makmur Cooperation. Internal consolidation in Gapoktan board continued with the preparation of cooperative establishment. Furthermore, a new cooperative members meeting, registration at the Notary, and the filing of a legal entity were the process of the cooperative establishment. Prerequisite condition for cooperative operation is the good financial and managerial performances. Supporting conditions is necessary for cooperative perform. Conducive business circumstance on cooperative core business is needed. Strengthening cooperative networking with strategic partners is main factor to increase the capacity of the cooperative effort.